2007
DOI: 10.1063/1.2720309
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of contact annealing: Ambipolar silicon nanowire transistor with improved performance

Abstract: High performance ambipolar silicon nanowire (SiNW) transistors were fabricated. SiNWs with uniform oxide sheath thicknesses of 6–7nm were synthesized via a gas-flow-controlled thermal evaporation method. Field effect transistors (FETs) were fabricated using as-grown SiNWs. A two step annealing process was used to control contacts between SiNW and metal source and drain in order to enhance device performance. Initially p-channel devices exhibited ambipolar behavior after contact annealing at 400°C. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 17 publications
4
34
2
Order By: Relevance
“…It also has been reported that the carrier mobility is sensitive to the electrical contacts between a metal and semiconductor [20]. The M-S-M model [23,24] applied to fit the data in figure 5 shows twofold lower carrier mobility than the annealed case [20]. The lower effective mobile-carrier density and mobility may explain the discrepancy between our work and [26], where the electrical contacts are Ohmic.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…It also has been reported that the carrier mobility is sensitive to the electrical contacts between a metal and semiconductor [20]. The M-S-M model [23,24] applied to fit the data in figure 5 shows twofold lower carrier mobility than the annealed case [20]. The lower effective mobile-carrier density and mobility may explain the discrepancy between our work and [26], where the electrical contacts are Ohmic.…”
contrasting
confidence: 56%
“…This electron density is comparable to the hole concentration in the initial p-type Si, and may make the SiNW almost intrinsic, leading to the lower current while still giving n-type FET characteristics. It also has been reported that the carrier mobility is sensitive to the electrical contacts between a metal and semiconductor [20]. The M-S-M model [23,24] applied to fit the data in figure 5 shows twofold lower carrier mobility than the annealed case [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion from unipolar p-type to ambipolar behavior, for instance, has been described for silicon nanowire FETs after vacuum annealing. [30] A marked increase in electron conduction has also been reported for nanoribbon graphene FETs after the devices were subjected to a similar treatment. [31] Thus, the effects of electrochemically mediated charge transfer to the O 2 /H 2 O redox couple appear to be ubiquitous, and have to be considered when interpreting the electrical behavior of all devices that have been exposed at one time or another to the ambient atmosphere.…”
mentioning
confidence: 85%
“…There are reports on the development of Si NW-based nanoscale devices such as field-effect transistors (FETs) [1,2] with wrap-around gates, surface-gated sensitive chemical and biomolecular sensors [3,4], as well as nanoscale opto-electronic devices [5]. In the context of such nanowire-based device, one important physical parameter is the low-frequency flicker noise, which has a direct impact on the device performance.…”
Section: Introductionmentioning
confidence: 99%